RELATIONSHIP OF PREGNANT WOMEN CLASSROOM WITH LEVEL OF ANXIETY WITH LABOR TO PREGNANT WOMAN TRIMESTER III IN JOGONALAN II PUBLIC HEALTH CENTER AREA - Murwati Murwati; Emy Suryani; Intan Kurniawati (Journal of Midwifery, 2018)
Anxiety is an unclear worried and widespread related to uncertain and helpless feelings. Anxiety before birth was questioning and wondering whether she could giving birth normally, how to push, whether something could happen during childbirth, and pain during labor. Anxiety in the third trimester of pregnant women can have an impact inhibiting the labor. Antenatal class is one form of counseling as an effort to overcome anxiety to face labour for third trimester pregnant mother. The aims of this study is to determine the relation of class participation of pregnant mother with the anxiety to face labour among third trimester pregnant woman. This was an observational analytic study with cross sectional design. The sample were the third trimester pregnant woman in Jogonalan II Klaten public health center area totalling 36 people using purposive sampling. The study instrument used was questionnaire of pregnant women's class participation and an anxiety rating scale (HARS) of the Hamilton Anxiety Rating Scale. Data analysis was performed using Spearman test. The results of this study shown that most of respondent age was 20-35 years which is 91.7%, high school education accounted for 52.8%, unemployed accounted for 69.4% and multigravida accounted for 63.9%. Antenatal class participation rate was 52.8% and mother who did not experience anxiety accouted for 63,9%. The result of statistical test obtained ρ = 0,001. There was an association between antenatal class participation with anxiety level in facing childbirth in third trimester pregnant women. Keywords: Antenatal class participation, anxiety of third trimester pregnant mother in facing childbirth